Model Kepercayaan Kesehatan terhadap Perilaku Pencegahan Penularan Covid-19 di Kota Padang - Erick Zicof; Rahmi Hidayanti; Darwel Darwel; Erika Erika; Elva Idriani (Poltekkes Kemenkes Padang, 2023)
Padang has the highest number of confirmed cases of COVID-19 in West Sumatera on 2021 as 18.328 with 334 deaths. The Health Belief Model (HBM) is a behavioral theory that seeks to explain healthy behavior by focusing on individual attitudes and beliefs. HBM is usually used to predict preventive behavior on disease prevention or health problems which considered priority, such as the COVID-19 outbreak. The purpose of the study was to determine the relationship between perceptions of vulnerability, severity, benefits, barriers and self-efficacy on the behavior of preventing COVID-19 transmission. The research method used is a cross-sectional approach with the number of research subjects as many as 100 samples. The research was implemented on April-October 2022. Data was collected using the fixed exposure sampling method with a ratio of cases and controls, namely 1:1. In COVID-19 prevention, it is obtained that there is a direct relationship between perceived seriousness with risk logit of 0.72 (p-value = 0.001), self-efficacy with risk logit of 0.14 (p-value = 0.035) and perception of vulnerability with risk logit of 0.10 (p-value = 0.005). while factors that are not directly related are the perception of barriers with a risk logit of 0.17 (p-value = 0.041) and the perception of benefits with a risk logit of 0.25 (p-value = 0.006). It is suggested to develop education related to the seriousness and severity of being infected with COVID-19.